Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Roy, Helen E; Bacher, Sven; Essl, Franz; Adriaens, Tim; Aldridge, David C; Bishop, John D D; Blackburn, Tim M; Branquart, Etienne; Brodie, Juliet; Carboneras, Carles; Cottier-Cook, Elizabeth J; Copp, Gordon H; et al. (Global change biology, 2019)
The European Union (EU) has recently published its first list of invasive alien species (IAS) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS. For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU. Experts then convened for a 2-day workshop applying consensus methods to compile a ranked list of potential IAS. From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.
Keywords: Animals; Consensus Development Conferences as Topic; ekosystém; konsensuální konference jako téma; Ecosystem; biodiverzita; Environmental Policy; hodnocení rizik; zvířata; Evropská unie; Introduced Species; zavlečené druhy; European Union; environmentální politika; Risk Assessment; Biodiversity